2014
DOI: 10.1155/2014/507197
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Potential ofTamarindus indicaon High Fat Diet Induced Nonalcoholic Fatty Liver Disease in Rats

Abstract: Nonalcoholic fatty liver disease (NAFLD), the prevalence of which is rising globally with current upsurge in obesity, is one of the most frequent causes of chronic liver diseases. The present study evaluated the ameliorative effect of extract of Tamarindus indica seed coat (ETS) on high fat diet (HFD) induced NAFLD, after daily administration at 45, 90, and 180 mg/kg body weight dose levels for a period of 6 weeks, in albino Wistar rats. Treatment with ETS at all tested dose levels significantly attenuated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…A large body of evidence supports a complex interaction between NAFLD and insulin resistance3536. In our study, the levels of fasting glucose and insulin resistance index were higher in HFD rats than in control rats.…”
Section: Discussionsupporting
confidence: 62%
“…A large body of evidence supports a complex interaction between NAFLD and insulin resistance3536. In our study, the levels of fasting glucose and insulin resistance index were higher in HFD rats than in control rats.…”
Section: Discussionsupporting
confidence: 62%
“…A large body of evidence supports a complex interaction between NAFLD and insulin resistance [28,29] . Some studies have suggested that abdominal adipose tissue has an important role in the development of insulin resistance [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is a great challenge for the pharmaceutical industry to develop a combined therapy that is effective in NAFLD patients exhibiting obesity, insulin resistance, dyslipidemia, and oxidative stress. Therefore, serious efforts have been directed to explore novel therapeutic agents that may be directed to multiple targets [ 52 ], natural products extracted from medicinal plants being rich sources of biologically active substances having effects on health benefits and disease prevention in humans [ 53 ]. Accordingly, current investigations have focused on herbal extracts and natural products with antihyperlipidemic and hepatoprotective effects against NAFLD [ 54 ], particularly potential sources of antioxidants [ 55 ] ( Table 3 ).…”
Section: Therapeutic Agentsmentioning
confidence: 99%
“…At present time, Tamarindus indica Linn is one of the most important resources of plants for supply of foods and materials [ 52 ]. Considering that the seed coat of tamarind contains polyphenols including tannins, anthocyanins, and anthocyanidin oligomers, Sasidharan et al [ 52 ] evaluated the ameliorative potential of seed coat of Tamarindus indica (ETS) extracts on HFD-induced NAFLD in rats.…”
Section: Therapeutic Agentsmentioning
confidence: 99%